Bone regeneration with micro/nano hybrid-structured biphasic calcium phosphate bioceramics at segmental bone defect and the induced immunoregulation of MSCs. (December 2017) - Zhu, Yu; Zhang, Kun; Zhao, Rui; Ye, Xingjiang; Chen, Xuening; Xiao, Zhanwen; Yang, Xiao; Zhu, Xiangdong; Zhang, Kai; Fan, Yujiang; Zhang, Xingdong
Abstract: Adequate bone regeneration has been difficult to achieve at segmental bone defects caused by disease. The surface structure and phase composition of calcium phosphate bioceramic are crucial for its bioactivity and osteoinductivity. In the present study, biphasic calcium phosphate (BCP) bioceramics composed of micro-whiskers and nanoparticles hybrid-structured surface (hBCP) were fabricated via a hydrothermal reaction. The in vivo long bone defect model of beagle dogs implanted with hBCP bioceramics achieved a higher quality regenerated bone as compared to the traditional smooth-surface BCP control group. After a 12-week implantation period, more new bone formation within the implanted material and a higher fracture load were observed in the hBCP group (p < 0.05 vs. control). In addition, the local bone integration efficacy, as determined by nanoindentation, showed a significantly closer elastic modulus of the implanted hBCP bioceramics to that of the natural bone adjacent. Finally, in vitro gene microarray analysis of the mesenchymal stem cells (MSCs) co-cultured with two bioceramics showed that the hBCP group induced a drastic downregulation of the genes associated with inflammatory response, which was never documented in previous studies regarding biomaterials with a micro/nano hybrid structure. The tumor necrosis factor (TNF) signalling pathway was the most involved and preferentially inhibited by the hBCP material. Collectively, the findings suggested that the micro/nano hybrid-structured bioceramics augmented local bone regeneration at segmental bone defects and presented a potential alternative to autologous bone grafts.